The Fucoxanthin Chlorophyll a/c-Binding Protein in Tisochrysis lutea: Influence of Nitrogen and Light on Fucoxanthin and Chlorophyll a/c-Binding Protein Gene Expression and Fucoxanthin Synthesis - Pajot, Anne; Lavaud, Johann; Carrier, Gregory; Garnier, Matthieu; Saint-Jean, Bruno; Rabilloud, Noémie; Baroukh, Caroline; Bérard, Jean-Baptiste; Bernard, Olivier; Marchal, Luc; Nicolau, Elodie (Frontiers in Plant Science, 2022)
We observed differences in lhc classification in Chromista. We proposed a classification of the lhcf family with two groups specific to haptophytes, one specific to diatoms, and one specific to seaweeds. Identification and characterization of the Fucoxanthin and Chlorophyll a/c-binding Protein (FCP) of the haptophyte microalgae Tisochrysis lutea were performed by similarity analysis. The FCP family contains 52 lhc genes in T. lutea. FCP pigment binding site candidates were characterized on Lhcf protein monomers of T. lutea, which possesses at least nine chlorophylls and five fucoxanthin molecules, on average, per monomer. The expression of T. lutea lhc genes was assessed during turbidostat and chemostat experiments, one with constant light (CL) and changing nitrogen phases, the second with a 12 h:12 h sinusoidal photoperiod and changing nitrogen phases. RNA-seq analysis revealed a dynamic decrease in the expression of lhc genes with nitrogen depletion. We observed that T. lutea lhcx2 was only expressed at night, suggesting that its role is to protect from return of light after prolonged darkness exposure.